Drug-related immune-mediated myelopathies - Gritsch, David; Valencia-Sanchez, Cristina (Frontiers in Neurology, 2022)
Iatrogenic immune-mediated inflammatory disorders of the spinal cord are an uncommon but potentially severe complication of drug therapy for several human diseases. Particularly the introduction of novel biological agents in the treatment of systemic inflammatory disorders and cancer immunotherapy have led to a significant increase in immune-related adverse events of the central nervous system (CNS). The use of Tumor necrosis factor alpha (TNF-alpha) inhibitors in rheumatic and inflammatory bowel diseases has been associated with demyelinating and other inflammatory CNS conditions, including myelitis. The introduction of immune checkpoint inhibitors in the treatment of several human malignancies has led to an increase in drug-induced immune-related adverse events including in the CNS. Other drugs that have been associated with immune-mediated myelitis include tyrosine-kinase inhibitors and chimeric antigen receptor (CAR) T-cell therapy. A high degree of suspicion is necessary when diagnosing these conditions, as early diagnosis and treatment is crucial in preventing further neurological damage and disability. The treatment of drug-induced inflammatory myelitis typically involves administration of high-dose intravenous corticosteroids, however additional immunosuppressive agents may be required in severe or refractory cases. While most cases are monophasic and remit following discontinuation of the offending agent, chronic immunosuppressive therapy may be indicated in cases with a progressive or relapsing disease course or when a diagnosis of a specific underlying neuro-inflammatory disorder is made. Outcomes are generally favorable, however depend on the specific therapeutic agent used, the clinical presentation and patient factors. In this review we aim to describe the clinical characteristics, imaging findings and management for the most common forms of iatrogenic immune-mediated myelopathies.